2016
DOI: 10.1021/acscatal.6b01884
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Enzyme/Whole-Cell Biotransformation of Plant Oils into C9 Carboxylic Acids

Abstract: Oxyfunctionalization of plant oils such as olive oil and soybean oil into C9 carboxylic acids (e.g., n-nonanoic acid and 9-hydroxynonanoic acid) was investigated. The biotransformation was composed of hydrolysis of plant oils by the Thermomyces lanuginosus lipase (TLL) and C9−C10 double-bond cleavage in unsaturated fatty acids by a serial reaction of a fatty acid double bond-hydratase of Stenotrophomonas maltophilia, an alcohol dehydrogenase of Micrococcus luteus, and a Baeyer−Villiger monooxygenase (BVMO) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 52 publications
(52 reference statements)
0
58
0
1
Order By: Relevance
“…strain DS5, which was used to oxygenate fatty acids, thus leading to 10-ketostearic acid as major product and a minor amount of 10-hydroxystearic acid when starting from olive oil [63]. Candida rugosa can also be used for the hydrolysis of safflower oil [43], as well as perilla seed oil [55,64] and tree oils [65]. The lipase Furthermore, several examples of the synthesis of hydroxy fatty acids, starting from the cleavage of the oils (Figure 2), have been demonstrated, and in the following, some selected examples are given.…”
Section: Substrate Loadingmentioning
confidence: 99%
“…strain DS5, which was used to oxygenate fatty acids, thus leading to 10-ketostearic acid as major product and a minor amount of 10-hydroxystearic acid when starting from olive oil [63]. Candida rugosa can also be used for the hydrolysis of safflower oil [43], as well as perilla seed oil [55,64] and tree oils [65]. The lipase Furthermore, several examples of the synthesis of hydroxy fatty acids, starting from the cleavage of the oils (Figure 2), have been demonstrated, and in the following, some selected examples are given.…”
Section: Substrate Loadingmentioning
confidence: 99%
“…The olive oil hydrolysate from lipase treatment was also successfully transformed by the cascade to give ω‐hydroxynonanoic acid in 60 % conversion. This whole‐cell cascade biotransformation was further improved by using a new hydratase with high activity and introducing a fatty acid transporter (FadL) to increase the uptake of substrates . In another following‐up study, the ω‐hydroxy acids produced in the above biotransformation were further oxidized to α,ω‐dicarboxylic acids or aminated to ω‐amino acids with E. coli expressing AlkJ or together with an ω‐transaminase (Scheme c) .…”
Section: Recent Development Of Whole‐cell Cascade Biotransformationsmentioning
confidence: 99%
“…The expression of the outer membrane protein AlkL, an alkane uptake facilitator in Pseudomonas putida GPo1, significantly increased the uptake of alkanes and linear esters in E. coli cells, and boosted the overall cascade transformations . Overexpression of FadL, a fatty acid transporter, in E. coli also showed benefits for whole‐cell biotransformation of fatty acids . On the other hand, the export of final product out of cells could relieve the product toxicity and inhibition, thus leading to higher product titer.…”
Section: Challenges and Potential Improvement Of Whole‐cell Cascade Bmentioning
confidence: 99%
“…In a previous study the hydrolysis of plant oils was reported using the Thermomyces lanuginosus lipase (TLL) and subsequent C9−C10 double‐bond cleavage in unsaturated fatty acids. The cascade reaction encompassed a fatty acid double‐bond hydratase from Stenotrophomonas maltophilia , an alcohol dehydrogenase from Micrococcus luteus (SADH), and a Baeyer‐Villiger monooxygenase (BVMO) from Pseudomonas putida KT2440 expressed in E. coli …”
Section: Hybrid In Vitro and In Vivo Cascadesmentioning
confidence: 99%